Literature Review: Lemon Aromatherapy Affected the Emesis Gravidarum in First Trimester Pregnancy - Nelil Mudarris; Siti Julaila; Mutiara Ayu Muthitulsalimah; Agus Rahmadi (STIKes Patria Husada Blitar, 2023)
Emesis occurs in 60-80% of primigravida and 40-60% of multigravida. These symptoms become more severe in one hundred out of a thousand pregnancies. The feeling of nausea is caused by an increase in estrogen and HCG hormone levels in the serum. 40% of women have used lemon scent to alleviate nausea and vomiting, and 25% of them have acknowledged that citrus aromatherapy is an effective way to control these symptoms. This study was aimed to determine the effectiveness of lemon aromatherapy in reducing emesis gravidarum in the first trimester of pregnancy. The method used a literature review. Research articles were searched using Google Scholar by entering the keywords